ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN DAN PENGARUHNYA TERHADAP MINAT MEREFERENSIKAN PELAYANAN RAWAT JALAN PADA RS. PKU MUHAMADIYAH GUBUG KABUPATEN GROBOGAN - Sugiharti, Ibu (STIE Totalwin Semarang, 2010)
Hospital is one of type effort for service that is now stays in very tightening emulation climate. Struggle to create recuring business with customer occupies central point in the effort hospital to exeed at long-range emulation. Service quality and cutomer value becomes thing which necessary for hospital. This research analysis factors influence customer satisfaction to create hospital service reference enthusiasm in Hospital PKU Muhamadiyah Gubug Kabupaten Grobogan. Research problem is existence of gap or debate at antecedent research would consequence and from customer satisfaction. Other problems is the happening of downdraft of number of outpatients continually at last four months and existence of improvement of number sighs from patient. Respondent in this research 120 patients with sampling method applies acidental sampling. This research applies analysis Structural Equation Modeling (SEM) what implemented through program AMOS as a means of assists its the analysis. Result of research proves that service quality, cutomer value and excellence of product has positive influence and signifikan to customer satisfaction. Hereinafter, customer satisfaction of influence positive and signifikan to hospital service reference enthusiasm. Excelsior service quality and cutomer value has customer satisfaction of excelsior and causes home service reference enthusiasm which excelsior.